Statements - Art 29'98 Messe Basel : Young Art : 26 One Person Shows. - Art Basel Basel 1998; Amer, Ghada; Antezzo, Matthew; Berger, Ralf; Dean, Tacita; Dikeau, Devon; Draeger, Christoph; Edmier, Keith; Gallo, Claudia Di; von Hausswolff, Annika; Hemmert, Hans; Hoffmann, Leni; et al. (Basel : ART Internationale Kunstmesse, 1998)
Valldosera, Eulàlia ; Manetas, Miltos ; Hausswolff, Annika von ; Mohr, Max ; Magnin, Stéphane ; Lipski, Edward ; Krisanamis, Udomsak ; Amer, Ghada ; Neto, Ernesto ; Berger, Ralf ; Pancrazzi, Luca ; Gallo, Claudia Di ; Kinoshita, Suchan ; Kentridge, William ; Dean, Tacita ; Hemmert, Hans ; van Warmerdam, Marijke ; Kern, Stefan ; Dikeou, Devon ; Antezzo, Matthew ; Draeger, Christoph ; Pernice, Manfred ; Majerus, Michel ; Edmier, Keith ; Walker, Kara ; Hoffmann, Leni
Duits
Engels
Young Art : 26 one persons shows / Junge Kunst : 26 Einzelausstellungen, Art Basel, 10.-15.6.1998
boek